Production of Membrane Proteins for NMR Studies Using the Condensed Single Protein Production (cSPP) System - Mao, Lili (2009)
In the Single Protein Production (SPP) method, all E. coli cellular mRNAs are eliminated by the induction of MazF, an ACA-specific mRNA interferase. When an mRNA for a membrane protein, engineered to have no ACA sequences without altering its amino acid sequence, is induced in the MazF-induced cells, E. coli is converted into a bioreactor producing only the targeted membrane protein. Here we demonstrate that three prokaryotic inner membrane proteins, two prokaryotic outer membrane proteins, and one human virus membrane protein can be produced at very high levels, and assembled in appropriate membrane fractions. The condensed SPP (cSPP) system was used to selectively produce isotope-enriched membrane proteins for NMR studies in up to 150-fold condensed culture without affecting protein yields, providing more than 99% cost saving for isotopes. As a novel application of the cSPP system for studies of membrane proteins prior to purification we also demonstrate, for the first time, fast detergent screening by microcoil NMR and well-resolved NMR spectra of several targeted integral membrane proteins obtained without purification.